Stem cell-based therapy for inflammatory bowel disease - Shimizu, Hiromichi (Intest Res, 2019)
Inflammatory bowel disease (IBD) is an idiopathic, multi-etiological disease characterized by inflammation and mucosal destruction of the gastrointestinal tract. Despite the remarkable advance in immunomodulating therapies, there still remains a certain population of patients who are refractory to conventional as well as biologic therapies and fail to achieve mucosal healing. To improve the prognosis of those patients, at least 2 types of stem cells have been tested for their potential therapeutic use. Transplantation of hematopoietic stem cells or mesenchymal stem cells have been tested in several clinical studies, but their beneficial effect still remains controversial. In this review, we would like to overview the recent clinical challenges of stem cell-based therapies in IBD and also introduce our new therapeutic plan of intestinal stem cell transplantation for IBD, based on our ex vivo intestinal organoid culture technique.